Pengaruh Pemberian Low Impact Aerobic Exercise Terhadap Penurunan Tekanan Darah Pada Lansia Di RW 10 Kelurahan Jatiwarna Kota Bekasi - Rovika Trioclarise; Ratu Karel Lina; Meiline Vannesa H; Putri Nabilah; Cholifah Nur Maulida; Rahma Widayanti; Mohammad Reza Syahputra (IFI cabang Kota Bekasi, 2023)
Background: Elderly is the advanced stage of a life process characterized by a decrease in the body's ability to adapt to environmental stress. One that occurs in the elderly is changes in the cardiovascular system which is the main disease that takes its toll because it will have an impact on other diseases such as hypertension, coronary heart disease, pulmonary heart, cardiomyopathy, stroke, kidney failure. Hypertension is defined as high blood pressure with systolic pressure ≥ 140 mmHg and diastolic pressure ≥ 90 mmHg. One way that can be done to reduce and control blood pressure is by giving low impact aerobic exercise. Low impact aerobic movements given to the elderly who experience hypertension will increase oxygen in the blood so that it can reduce adrenaline hormone levels. This movement also serves to improve heart function, muscle strength and flexibility, improve the cardiorespiratory system, and reduce the risk of fat accumulation in blood vessels so that their elasticity is maintained. Objective: Knowing the effect of low impact aerobic movements on lowering blood pressure in the elderly who suffer from hypertension. Methods: This community physiotherapy activity uses a community-based approach. Students make direct observations accompanied by a supervisor. Students carry out community activities in RW 10 every 1 week for 4 hours and are carried out for 5 weeks, to see the problems that often occur in the elderly in RW 10 Jatiwarna Village, Bekasi City. This community physiotherapy activity is divided into several stages, namely: (1) preparation; general health check (blood pressure, blood sugar, and cholesterol), (2) implementation; low impact aerobic movement, and (3) evaluation. Results: Community physiotherapy activities carried out by providing low impact aerobic exercise interventions showed that the percentage of elderly people who had high blood pressure decreased significantly from 67% of elderly people with high blood pressure to 56% percent. Conclusion: Low impact aerobic exercise has an effect in reducing high blood pressure in the elderly.